Designing Augmented Reality-Based Multimedia Using Experimental Methods to Improve Students' Cognitive in Basic Network Subject - Sumitra, Desfasa Ilham; Setiawan, Wawan; Rasim, Rasim (Universitas Pendidikan Indonesia, 2023)
This study aims to determine the cognitive increase that occurs in students, after being given treatment in the form of learning using-based learning multimedia Augmented Reality with VAK (learning models Visualization, Auditory, Kinesthetic) in Basic Network subjects. The subjects of this study were students of class X (ten) at one of the vocational schools in the district, West Bandung. The background of this research is the learning model used previously in the teaching process is less effective, the multimedia used by the teacher is too monotonous and the lack of understanding and student activity in the learning process. The research method used in this research is quantitative and the teaching method used is experimental. While the application development method used is SHM (Comprehensive Life Cycle) and the results obtained from this study are: 1) Interactive multimedia is considered good and suitable for use. The presentation score was 83.99% which was interpreted as